記憶的寓言——論白先勇與“臺北/人”小説書寫的脈絡: Pai Hsien-yung and Taipei/Taipei People in Post-War Taiwan Fiction
<span data-sheets-value=""1":2,"2":"LANGUAGE NOTE | Document text in Chinese; abstract also in English."" data-sheets-userformat=""2":705,"3":"1":0,"9":0,"10":1,"12":0" data-sheets-validation-definition=""1":"1":"1":24,"2":["1":0,"5":"1":"1":0,"2":"1":2,"2":"LANGUAGE NOTE | Document text in Chinese; abstract also in English." ,"1":0,"5":"1":"1":0,"2":"1":2,"2":"LANGUAGE NOTE | Document text in Chinese only." ],"2":"1":"1":["1":4,"6":0,"1":2,"3":"TRIM","4":1,"1":3,"5":"1":2,"2":"LANGUAGE NOTE | Document text in Chinese; abstract also in English." ,"1":3,"5":"1":2,"2":"LANGUAGE NOTE | Document text in Chinese only." ,"1":2,"3":"ARRAY_ROW","4":2,"1":2,"3":"ARRAY_LITERAL","4":1,"1":2,"3":"TRIM","4":1,"1":2,"3":"EXACT","4":2,"1":2,"3":"OR","4":1,"1":2,"3":"ARRAYFORMULA","4":1,"1":1,"2":"="],"3":"R0]FTRIM:1]LSLANGUAGE NOTE | Document text in Chinese; abstract also in English.]]LSLANGUAGE NOTE | Document text in Chinese only.]]FARRAY_ROW:2]FARRAY_LITERAL:1]FTRIM:1]FEXACT:2]FOR:1]FARRAYFORMULA:1]S","3":["1":"1":0,"2":1,"3":0,"4":1,"5":1118464,"2":0],"2":"","3":0,"4":1" data-sheets-validation-id="0">LANGUAGE NOTE | Document text in Chinese; abstract also in English. <span data-sheets-value=""1":2,"2":"LANGUAGE NOTE | Document text in Chinese; abstract also in English."" data-sheets-userformat=""2":705,"3":"1":0,"9":0,"10":1,"12":0" data-sheets-validation-definition=""1":"1":"1":24,"2":["1":0,"5":"1":"1":0,"2":"1":2,"2":"LANGUAGE NOTE | Document text in Chinese; abstract also in English." ,"1":0,"5":"1":"1":0,"2":"1":2,"2":"LANGUAGE NOTE | Document text in Chinese only." ],"2":"1":"1":["1":4,"6":0,"1":2,"3":"TRIM","4":1,"1":3,"5":"1":2,"2":"LANGUAGE NOTE | Document text in Chinese; abstract also in English." ,"1":3,"5":"1":2,"2":"LANGUAGE NOTE | Document text in Chinese only." ,"1":2,"3":"ARRAY_ROW","4":2,"1":2,"3":"ARRAY_LITERAL","4":1,"1":2,"3":"TRIM","4":1,"1":2,"3":"EXACT","4":2,"1":2,"3":"OR","4":1,"1":2,"3":"ARRAYFORMULA","4":1,"1":1,"2":"="],"3":"R0]FTRIM:1]LSLANGUAGE NOTE | Document text in Chinese; abstract also in English.]]LSLANGUAGE NOTE | Document text in Chinese only.]]FARRAY_ROW:2]FARRAY_LITERAL:1]FTRIM:1]FEXACT:2]FOR:1]FARRAYFORMULA:1]S","3":["1":"1":0,"2":1,"3":0,"4":1,"5":1118464,"2":0],"2":"","3":0,"4":1" data-sheets-validation-id="0">臺北爲臺灣戰後首要城市，集中了大量文化與政治資源，戰後因爲國共争鬥遷臺的大陸移民，亦有相當數量選擇以臺北爲居住地。這些政治性移民懷抱著家國之思，接受了國民政府打造的復國神話。長期以來處在兩岸的現實對立中，以及鄉愁的牽扯，這些也成爲戰後大陸移民第一代寫作的主要内容。而在臺灣成長的大陸移民下一代，因爲年歲不同以及大陸經驗之多寡有無，加上七十年代以來日漸抬頭的鄉土或本土意識衛擊，和都市擴張與族群記憶的關係，自我認同起了變化，對自己的上一代、自己所屬的族群和“中國”，也抱持著不一樣的態度。 <span data-sheets-value=""1":2,"2":"LANGUAGE NOTE | Document text in Chinese; abstract also in English."" data-sheets-userformat=""2":705,"3":"1":0,"9":0,"10":1,"12":0" data-sheets-validation-definition=""1":"1":"1":24,"2":["1":0,"5":"1":"1":0,"2":"1":2,"2":"LANGUAGE NOTE | Document text in Chinese; abstract also in English." ,"1":0,"5":"1":"1":0,"2":"1":2,"2":"LANGUAGE NOTE | Document text in Chinese only." ],"2":"1":"1":["1":4,"6":0,"1":2,"3":"TRIM","4":1,"1":3,"5":"1":2,"2":"LANGUAGE NOTE | Document text in Chinese; abstract also in English." ,"1":3,"5":"1":2,"2":"LANGUAGE NOTE | Document text in Chinese only." ,"1":2,"3":"ARRAY_ROW","4":2,"1":2,"3":"ARRAY_LITERAL","4":1,"1":2,"3":"TRIM","4":1,"1":2,"3":"EXACT","4":2,"1":2,"3":"OR","4":1,"1":2,"3":"ARRAYFORMULA","4":1,"1":1,"2":"="],"3":"R0]FTRIM:1]LSLANGUAGE NOTE | Document text in Chinese; abstract also in English.]]LSLANGUAGE NOTE | Document text in Chinese only.]]FARRAY_ROW:2]FARRAY_LITERAL:1]FTRIM:1]FEXACT:2]FOR:1]FARRAYFORMULA:1]S","3":["1":"1":0,"2":1,"3":0,"4":1,"5":1118464,"2":0],"2":"","3":0,"4":1" data-sheets-validation-id="0">產生於五十到七十年代的白先勇小説，是戰後臺灣小説明確以外省移民最多的臺北爲主題的小説，多描述戰後大陸移民在臺北的生活情況和家國之悲，這一寫作的底蘊因爲族群問題始终未曾消弭，在不同年代的外省籍寫作者身上遂有特殊的表現。八十年代以降，李渝、朱天文、朱天心、駱以軍，這幾位在臺灣成長或居住的“外省籍”小説家，延續對“臺北/人”的關注，家國之悲却已然轉化，“臺北”的地位不再是鄉愁的副本，反而成爲記憶的源頭、生命的救贖，或被視爲是新故鄉所在。特别是較年輕的朱家姊妹和駱以軍，他們身在臺灣，感受政治、族群和都市變化較深，也更加强了小説内無所不在的“孤兒”意識。 Taipei, as the provisional capital of the Republic of China, emerged as the pre-eminent center of cultural and political resources in post-war Taiwan, and became home to large numbers political refugees from the Chinese mainland. In face of the protracted confrontation across the Taiwan straits, these refugees upheld the myth of returning the mainland, harboring homesickness and an “obsession with China” that became the fundamental theme in the first generation immigrants’ works of fiction. Over time, however, the widening generational gap between the first-generation immigrants (waishengren/ waishengji) and their Taiwan-born and -raised offspring produced changing identities: the emerging nativist movement of the 1970s, urbanization, and changing collective memories all factored in a different attitude toward the older generation, toward their own ethnic group, and towards “China”. Pai Hsien-yung’s fiction from the 50s to the 70s centers on Taipei with its large immigrant population, on their lives and their grief, making Taipei into an imagined China. Yet the Taipei/ Taipei people theme figures prominently not only in the works of the waishengji writers of this generation: since the 1980s, Taiwan-born or -raised waisheng writers such as Li Yu, Zhu Tianwen, Zhu Tianxin, and Luo Yijun, too, have framed Taipei/Taipei people in their fiction, refocusing their attention, however, to “Taipei” as a source of memory, an anchoring ground, and a new home- and thus entirely redefining its cultural significance. The Zhu sisters and Luo Yijun in particular develop an intensive awareness of the political and ethnical changes taking place around them, and of the rapid urbanization, developments that find reflection in their works in form of an omnipresent “orphan awareness". , journal=人文中國學報, author=楊佳嫻, year=2005, month=Aug., pages=539–575